An Update on Cardiovascular Risk Factors After Kawasaki Disease - Zeng, Yuan-Yuan; Zhang, Min; Ko, Syeun; Chen, Feng (Frontiers in Cardiovascular Medicine, 2021)
First described in Japan 50 years ago, Kawasaki disease is a worldwide multisystem disease. It is an acute self-limited vasculitis of unknown etiology that can lead to coronary artery lesions, such as dilatation, aneurysms, and stenosis in children. It is one of the common causes of acquired heart disease among children in developed countries. The coronary aneurysm is a severe complication in the acute stage, possibly leading to stenotic lesions or myocardial ischemia. More concerns have centered on endothelial damage and the early onset of atherosclerosis in patients with KD. Although the coronary artery aneurysm is small or degenerated, the vascular structure does not return to normal, vascular endothelial dysfunction and remodeling continue. Most patients diagnosed with coronary artery sequelae are at risk of long-term complications. There are still many unknown aspects regarding the long-term prognosis of patients. Concerns have centered on the early onset of atherosclerosis in patients with KD. There is still no consensus on the relationship between Kawasaki disease and atherosclerosis. This study aimed to evaluate if patients with a history of KD were at risk of accelerated atherosclerosis.